Esau, Son of Isaac and Grandson of Abraham: The Model of a Faithful Son - Reiss, Moshe (The Asbury journal, 2014)
The story of Esau and Jacob, the two powerful sons of Isaac and Rebekah is one of the several conflicting families noted in the book of Genesis. Jacob, whose other name is Israel, is the father of the twelve tribes and thus the founder of the Jewish people. Rebekah may be the most pow- erful of the matriarchs; the one God talks to directly about her role in the covenant. The reconciliation of the brothers is one of the more powerful descriptions in the Bible.